Mathematical modeling and visualization of gas transport in a zeolite bed using a slice selection procedure - Petryk, Mykhaylo; Leclerc, Sebastien; Canet, Daniel; Fraissard, Jacques (Diffusion Fundamentals, 2007)
We present the analytical solution of the equations of gas diffusion in a heterogeneous zeolite bed. The problem is handled by assuming that the bed consists of a large number of very thin layers of solid, perpendicular to the direction of propagation of the gas. Mass transfer by diffusion in such a material is determined by a system of differential equations with boundary and interface conditions. The results allow the theoretical determination of the time dependence of the concentration profiles and the inter- and intra-crystallite diffusion coefficients of a gas in each layer of the bed. A numerical application concerns the diffusion of benzene in a cylindrical bed of ZSM5 displaced vertically and rapidly, step by step, inside the NMR probe. Thus we can obtain the time dependence of the concentration of gas absorbed at the level of each slice. These coupled investigations give a better understanding of the diffusion process in this multilayer material.